International ethics concepts, theories, and cases in global politics - Amstutz, Mark R. (Rowman & Littlefield Publishers, 2013)
Now in a comprehensively revised and updated edition, International Ethics cogently demonstrates that moral values and ethical reasoning are indispensable in global politics. Through balanced arguments and a wide-ranging selection of case studies, Mark R. Amstutz convincingly demonstrates that moral norms are an essential element of foreign policy and that ethical analysis is central to the study of international relations. Amstutz illustrates the role of moral norms in global politics with twenty-five revised and new case studies. The cases are focused on eight major global issues: political reconciliation, human rights, war, irregular war, foreign intervention, economic sanctions, justice among states, and global justice. This clearly written study will be of special interest to students and practitioners of international affairs who are concerned with the role of political morality and ethical judgment in global affairs.